Christianity and the Worldview of the Kelabit Society, Sarawak, Malaysia - Hee, Chan Jung (2009)
The purpose of this study was to examine Christianity and the worldview of Kelabit society, which is one of the small indigenous groups in Sarawak, East Malaysia. There were four objectives outlined in this study. Firstly, the study examined the spread of Christianity in the Kelabit highlands, Sarawak and Malaysia. Secondly, it was carried out to determine the religiosity of the Kelabit. Thirdly, it was done to identify the worldview of the Kelabit, and finally it was aimed at analyzing the social changes experienced by the Kelabit society and their worldview. Both qualitative and quantitative research methods were applied for this study. Data from the qualitative research were collected through in-depth interview with fortyone respondents who were selected from among social, religious and educational leaders of the Kelabit society. Participant observation was also conducted by the researcher in the villages in Bario, Sarawak. Meanwhile, qualitative data were arranged by encoding them into thirteen topics. The topics were classified by three important themes, which included religiosity of Christianity, worldview and social changes of the Kelabit. The qualitative data were analyzed by interpreting according to the three main themes. In addition, the quantitative data were also obtained by distributing one hundred questionnaires among the Kelabits who are residing in Kelabit Highlands, Miri, Kuching and Kuala Lumpur. The quantitative data were analyzed using SPSS version 15.0. There are four findings yielded in this research. Firstly, the Kelabit society has been influenced by the spread of Christianity through the Australian and American missionaries in the early stage. As a result, the Kelabits converted to Christianity and experienced the Christian revival. Secondly, the Kelabit has unique religious practices which include various church activities such as early morning prayers and worships. Moreover, their religiosity is strongly related to their social lifestyles. Thirdly, the present worldview of the Kelabits is influenced through the years by animism, Christianity and Christian revival. Finally, the study also revealed that the worldview of the Kelabits has shaped their society.